1978
DOI: 10.1002/pssb.2220860122
|View full text |Cite
|
Sign up to set email alerts
|

Phase transition in the mixed crystals TbpY1−pAsO4

Abstract: The energy of the four lowest crystal field levels of Tb3+ in the mixed crystals Tb,Y1 -pA804 i s investigated in the range of the crystallographic and magnetic phase transition as a function of temperature and Tb-concentration (0.2 < p 1). The results show that, in contrast to the magnetic ordering, the interaction causing the crystallographic transition is of long range and hence a simple molecular field theory fits the experimental data. For small Tb-concentrations, the feature of this system are superimpos… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
8
0

Year Published

1984
1984
2021
2021

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 7 publications
(8 citation statements)
references
References 16 publications
0
8
0
Order By: Relevance
“…This does not allow comparing the calculation results with the experimental data for the systems under study. At the same time, polymorphic transitions in solid solutions of the Tb x Y 1x AsO 4 and Tb x Tm 1x AsO 4 systems at temperatures below 30 K were previously studied [24,25]. It was found that, in the Tb x Y 1x AsO 4 system, the temperature of the phase transition from tetragonal symmetry to rhombic one increases regularly from 5.8 to 27.3 K when x varies from 0.32 to 1, and in the Tb x Tm 1x AsO 4 system, when x changes from 0 to 1, it increases from 6.1 to 25.5 K [24,25].…”
Section: Calculation Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…This does not allow comparing the calculation results with the experimental data for the systems under study. At the same time, polymorphic transitions in solid solutions of the Tb x Y 1x AsO 4 and Tb x Tm 1x AsO 4 systems at temperatures below 30 K were previously studied [24,25]. It was found that, in the Tb x Y 1x AsO 4 system, the temperature of the phase transition from tetragonal symmetry to rhombic one increases regularly from 5.8 to 27.3 K when x varies from 0.32 to 1, and in the Tb x Tm 1x AsO 4 system, when x changes from 0 to 1, it increases from 6.1 to 25.5 K [24,25].…”
Section: Calculation Resultsmentioning
confidence: 99%
“…At the same time, polymorphic transitions in solid solutions of the Tb x Y 1x AsO 4 and Tb x Tm 1x AsO 4 systems at temperatures below 30 K were previously studied [24,25]. It was found that, in the Tb x Y 1x AsO 4 system, the temperature of the phase transition from tetragonal symmetry to rhombic one increases regularly from 5.8 to 27.3 K when x varies from 0.32 to 1, and in the Tb x Tm 1x AsO 4 system, when x changes from 0 to 1, it increases from 6.1 to 25.5 K [24,25]. This indicates in the first case a wide range of formation of solid solutions, and in the second case, the presence of unlimited miscibility of components at temperatures of about 30 K.…”
Section: Calculation Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…[5][6][7][8][9][10][11][12][13][14][15][16][17] In general, a reduction of the transition temperature T D was observed in these mixed compounds. A modified molecular-field model was developed to explain the experimental data.…”
Section: Introductionmentioning
confidence: 99%
“…The temperature dependence of the order parameter and the specific heat were published only for mixtures distorting like TbV0, [14,17,19,201. For mixtures containing Dy3+, only the transition temperatures (and some dielectric data) are known [15,18,211.…”
Section: Introductionmentioning
confidence: 99%